Geração de valor em green buildings: um estudo sobre shopping centers no Brasil - Oliveira, Cristiano (2013)
The increasing public interest about the sustainability debate shows the importance of how investments in environmental projects are linked with business strategy and how managers perceive their value creation. This research investigated why real estate managers, more specifically the company Sonae Sierra Brazil (Shopping Centers industry), decide to adopt environmental prerogatives, specifically on Green Buildings. This exploratory research contributes to a better understanding of when adoption of this type of project creates value, by analyzing perception of company’s executives, competitors, and one of its main stakeholders: retail operations (tenants). Thus, interviews were conducted to observe different expressions of value normally perceived, or contrasting factors limiting these values, and compare if these values perceived by company managers are shared by their counterparts. The results indicated primarily intangible values such as corporate identity creation, enterprise integration and knowledge transfer and signaling to the market, to which it was not observed any specific restriction. The results also showed that certain types of value usually taken as relevant in motivating the adoption of these projects, such as differentiation and enhancing the brand values are often highlighted, but accompanied by questions and restrictions. It is expected, therefore, that the findings will contribute to deepening the understanding of how organizations realize demand for projects that are environmentally efficient and increase the perception of value that such projects provide, in order to foster informed decisions and formulating better public policies.